The Effect of Digital Marketing Activities on Purchase Decisions Through Electronic Word of Mouth (e-WOM) on Tiktok Platform - Nurazizah, Athifa Rahma; Salya, Aditya; Rafiah, Jurnia Khafidhatur; Sudarsono, Rachmat (Business Education Program of Universitas Pendidikan Indonesia, 2024)
The rapid growth of the internet has revolutionized marketing, making it more efficient through the use of digital technologies. Digital marketing is now believed to influence consumer purchasing behavior at cafes in Bandung. This study aims to examine the impact of digital marketing activities, specifically Marketing Content and Electronic Promotion, on the Purchasing Decisions of cafe customers in Bandung, with a focus on the mediating role of Electronic Word of Mouth (eWOM). Employing a quantitative descriptive approach and an online survey method, this research involved 201 Bandung residents who are active TikTok users and have patronized local cafes. Data was analyzed using PLS-SEM with SmartPLS 3.0. Findings indicate that both Marketing Content and Electronic Promotion have a significant positive influence on eWOM. Furthermore, all three variables (Marketing Content, Electronic Promotion, and eWOM) positively affect Purchasing Decisions; however, only Marketing Content and eWOM exhibit a statistically significant relationship. The study also confirms the mediating role of eWOM in the relationship between Marketing Content, Electronic Promotion, and Purchasing Decisions. For cafe businesses, creating interactive content such as reviews and experiences on TikTok is recommended to enhance visibility. Future research could delve deeper into or narrow down the scope of this study.